Structural Modification of Alginate Microbeads Containing Human Hepatocyte and Mesenchymal Stromal Cells as a Potential way to Improve Hepatic Functions for Cell Transplantation in Acute Liver Failure. (July 2018) - Iansante, Valeria; Dhawan, Anil; Lee, Charlotte; Dacosta, Raquel Fernandez; Fitzpatrick, Emer; Mitry, Ragai; Filippi, Celine
Abstract : Background and Aims: Biomaterial-combined cell therapies are currently of high interest for regenerative medicine. Alginate, a natural polysaccharide extracted from brown seaweed, has been investigated as a biocompatible hydrogel to encapsulate hepatocytes in microbeads (MB) for intraperitoneal transplantation in patients with acute liver failure (ALF). This approach allows donor cells to perform all the hepatic functions while the recipient's liver regenerates, thus potentially representing an alternative or a bridge to liver transplantation, without any need for immunosuppression. Our group has shown that co-encapsulation of human hepatocytes (HC) with mesenchymal stromal cells (MSC) significantly improves hepatic functions. Since the depolymerisation of the MB core should improve cell-to-cell contact, in this study we aimed to investigate whether this approach would further improve hepatocyte performance thus providing potential benefits in clinical applications. Method: Human primary HC and MSC were co-encapsulated in 4% alginate (Sigma) using a Buchi IE-50R encapsulator (Inotech Encapsulation AG) and sprayed into a 100mM CaCl2 bath. The resulting beads were divided equally into controls (CTR) or depolymerised (DP) through treatment with 1% poly-L-lysine, followed by immersion in 0.15% alginate and incubation in 50mM sodium citrate to dissolve the alginate core. MB were cultured in vitro up to 14 days. Cell viability was assessed by MTT assays, and albumin, alpha1-antitrypsin and urea production analysed to measure HC functions. Images were taken with Leica DMi8 microscope. All the results were obtained analysing n=9 samples performed in three separate experiments; results shown as mean±SEM Results: Cell viability did not show any significant difference within the two groups (Day 1: CTROD =0.62±0.24 vs DPOD =0.83±0.38; Day 3: CTROD =0.46±0.12 vs DPOD =0.60±0.24; Day 7: CTROD =0.20±0.01 vs DPOD =0.39±0.11; Day 14: CTROD =0.20±0.02 vs DPOD =0.27±0.05). Human albumin (ALB) and alpha1-antitrypsin (AAT) released into the supernatant showed comparable values over time in the two different conditions, similarly decreasing within 14 days to around 10% of the original value measured at Day 1. Similar results were observed for ureogenesis. Images of the microbeads were taken at different time points and showed a different internal structure in the microbeads after depolymerisation, however no signs of cell motility were observed. Conclusion: Our results did not show any significant difference between HC+MSC co-encapsulated in regular or core-depolymerised alginate MB, suggesting that the loss of alginate cross-linking in the microbead does not affect the overall cellular behaviour. The method based on regular encapsulation of cells in alginate microbeads without depolymerisation is simpler and can be more easily translated into clinical applications.